2017
DOI: 10.1093/cz/zox002
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis reveals that reproductive strategies are associated with sexual differences in oxidative balance across vertebrates

David Costantini

Abstract: Oxidative stress is a key physiological mechanism underlying life-history tradeoffs. Here, I use meta-analytic techniques to test whether sexual differences in oxidative balance are common in vertebrates and to identify which factors are associated with such differences. The dataset included 732 effect size estimates from 100 articles (82 species). Larger unsigned effect size (meaning larger sexual differences in a given marker) occurred in: reptiles and fish; those species that do not provide parental care; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 115 publications
3
33
1
Order By: Relevance
“…We found that pregnant female lizards had higher non‐enzymatic antioxidant capacity than males and experienced higher changes in oxidative status when resources are scarce. A common pattern in oviparous reptiles is for breeding females to exhibit higher sensitivity than male reptiles (Costantini, ). Here, we provided evidence that a viviparous species may also experience a potential extra‐cost of reproduction in females (Costantini, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that pregnant female lizards had higher non‐enzymatic antioxidant capacity than males and experienced higher changes in oxidative status when resources are scarce. A common pattern in oviparous reptiles is for breeding females to exhibit higher sensitivity than male reptiles (Costantini, ). Here, we provided evidence that a viviparous species may also experience a potential extra‐cost of reproduction in females (Costantini, ).…”
Section: Discussionmentioning
confidence: 99%
“…A common pattern in oviparous reptiles is for breeding females to exhibit higher sensitivity than male reptiles (Costantini, ). Here, we provided evidence that a viviparous species may also experience a potential extra‐cost of reproduction in females (Costantini, ). In Z. vivipara , all adult females ovulate during reproductive season and invest in egg production even in the absence of mating opportunity (Bleu, Le Galliard, Meylan, Massot, & Fitze, ), so non‐reproductive females were lacking in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work did not detect any significant sexual differences in oxidative status markers between herpesvirus-infected males and females in Magnificent frigatebird nestlings 20 . Sexual differences in oxidative status markers are also generally small to moderate in mammals, even if among species variation occurs 38 . We suggest that future studies should look at sex effects in more detail, comparing males and females across different demanding phases of life, where sexes might be faced with tradeoffs of greater or lesser magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in population longevity appear to be independent of sampling effort (see for example Gruber et al, 2015) and, although no precise record of age at maturity from our sites could be found, data from the western Atlantic suggests that it is variable among populations (Thompson et al, 1980) and likely correlated to longevity as it is in different bivalve species (Ridgway et al, 2011). As our understanding of oxidative stress increases, it appears that mitochondrial ROS management is at the center of modulation of life-history traits (such as reproduction and growth, see Costantini, 2018). We then suggest that the divergences in observed MRL among populations should not only be the consequence of detrimental effects of stressful conditions, but could also result from the adjustment of maturation to insure completion of the life cycle in the different environmental conditions experienced by the populations.…”
Section: Resultsmentioning
confidence: 99%